DEVELOPMENT POSSIBILITIES OF ORGANIC AGRICULTURAL IN SERBIA - Kostić-Nikolić, Slavica (Economics of Agriculture, 2006)
This article is analyzing the possible development of organic agricultural in Serbia. It is pointing on importance of legislation pass, organized purchase, organic goods market developing, achieving better competitiveness of the goods and also a reduction in usage of artificial fertilizers and pesticides.